Industrial potential of lipoxygenases. (3rd July 2016) - Heshof, Ruud; de Graaff, Leo H.; Villaverde, Juan J.; Silvestre, Armando J.D.; Haarmann, Thomas; Dalsgaard, Trine K.; Buchert, Johanna
Abstract: Lipoxygenases (LOXs) are iron- or manganese-containing oxidative enzymes found in plants, animals, bacteria and fungi. LOXs catalyze the oxidation of polyunsaturated fatty acids to the corresponding highly reactive hydroperoxides. Production of hydroperoxides by LOX can be exploited in different applications such as in bleaching of colored components, modification of lipids originating from different raw materials, production of lipid derived chemicals and production of aroma compounds. Most application research has been carried out using soybean LOX, but currently the use of microbial LOXs has also been reported. Development of LOX composition with high activity by heterologous expression in suitable production hosts would enable full exploitation of the potential of LOX derived reactions in different applications. Here, we review the biological role of LOXs, their heterologous production, as well as potential use in different applications. LOXs may fulfill an important role in the design of processes that are far more environmental friendly than currently used chemical reactions. Difficulties in screening for the optimal enzymes and producing LOX enzymes in sufficient amounts prevent large-scale application so far. With this review, we summarize current knowledge of LOX enzymes and the way in which they can be produced and applied.